Economic Feasibility Analysis of Saudi Clubs’ Investment in Player Health: An Applied Study on Athletic Performance - Balilah, Abdulrazak Mazen; Alawi, Fahad Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
Objectives: This study aims to evaluate the economic feasibility of investments made by Saudi sports clubs in player health. It specifically investigates the relationship between spending on health and fitness programs and their impact on athletic performance and financial returns. Methods: The research employed a descriptive-analytical approach combined with a case study methodology. Data collection tools included financial analysis, semi-structured interviews with club administrators, surveys with players and coaches, and comparative analysis between clubs that invest in player health and those that do not. Results: The findings indicate a positive relationship between investment in player health and improved athletic performance, which in turn has an indirect effect on financial returns. The study also revealed the absence of clear institutional policies governing health investments, despite increased awareness among stakeholders. Clubs that adopt structured health investment strategies demonstrated significantly higher competitiveness and financial stability compared to those that do not. Conclusions: The study recommends increasing budget allocations for health and fitness within sports clubs, forming strategic partnerships with medical institutions, and implementing periodic evaluation mechanisms to assess the athletic and financial impact of such investments.